TINGKAT KELANGSUNGAN HIDUP FRAGMEN KARANG Acroporaformosa YANG DITRANSPLANTASIKAN PADA MEDIA BUATAN YANG TERBUAT DARI PECAHAN KARANG (RUBBLE) - Nur Fadli (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Coral reefs around the world continue to decline.Corals killed by natural or anthropogenic disturbances are often degraded into rubble. This rubble is dynamic, easily shifted by storms and currents which may forms